Investigations on the chemical composition and tensile strength of steel bars in the Nigerian construction industry (2019)
Steel reinforcement bar compliments concrete in reinforced concrete structures to provide the required strength, rigidity and durability. This study investigates the level of conformity of reinforced steel bars available in the Nigerian construction industry through investigations on the percentage of chemical composition and tensile properties in relation to relevant local and international standards. Samples from 12 different companies were considered in this research. The chemical analysis results discovered 16 elements, some of which are residual elements in minute quantities. 9 samples had carbon content of less than 0.27%, 17 samples had phosphorus content less than 0.055%, 16 samples had sulphur content less than 0.055%, 9 samples had copper content less than 0.25% and 17 samples had carbon equivalent of less than 0.54% which are all requirements of NIS 117. Similarly, most of the samples examined did not meet the requirements of NIS 117 and BS4449 in respect of steel bar diameter, characteristic strength, ductility, ultimate to yield strength ratio, or a combination of the parameters with the yield strength ranging from 462.02 N/mm2 to 558.27 N/mm2. An indication of the level of quality of steel bars available in Nigerian construction industry can be deduced from the results of this research.